Methodological Innovation in Higher Education: The Use of Active Strategies in Face-to-Face and Virtual Modalities - Cano Lassonde, Olda María (2025)
This essay presents a documentary analysis on the impact of active and innovative methodologies in transforming the teaching-learning process in higher education. Based on a review of specialized literature, it emphasizes that these pedagogical strategies place students at the center of learning, promoting autonomy, critical thinking, problem-solving, collaboration, and active participation, both in face-to-face and virtual environments. Theoretical analysis underscores the necessity to redefine the faculty role as facilitators and students as active agents within a more inclusive, dynamic educational model aimed at meaningful learning. It highlights that implementing these methodologies implies a cultural shift in teaching, viewing learning as a constructive, contextualized, and interdisciplinary process. Additionally, the essay discusses the strategic use of digital technologies and educational platforms, which, when applied intentionally for pedagogical purposes, enhance personalization, autonomy, and flexibility in learning. Finally, it acknowledges that their effective incorporation requires faculty commitment, ongoing professional development, and institutional support to establish relevant and adaptive educational environments.